Kesatuan Bisnis dan Etika dalam al-Qur’an: Upaya Membangun Kerangka Bisnis Syariah - Muhamad Muhammad (Universitas Darussalam Gontor, 2013)
The integration of ethics and business or business and ethics can mean to impose religious norms upon business, to post ethical code for business, to revise the economic system and law, and to improve the skills of managing the demands of ethics from outside parties to seek for safe and so on. It implies that ethics is treated as a separate discipline and would be applied to the business world or to be developed by applying the study of moral issues in the business field. Such understanding will in turn lead to various branches of ethics such as economic ethics, business ethics, management ethics, banking ethics and others. At such levels, associated with this study, the questions are raised whether business and ethics in the Qur’an are separated or integrated; also how the Qur’an gives its perception about business and ethics. In Islam, Al-Quran provides a clear guidance for business vision which is a future business vision which is not only aiming at a short term profit which includes harm but a kind of profit which is essentially good and having a good effect at its end. In other words, Ethics and Business are an integrated unity. As the result, the business growth in Islam is a function of profit, satisfaction of customer and other factors which cannot be detected and at the same time influencing the business success and the approval of Allah.